Liver trauma - Nitto, Daniel; Spano, Cosme; Musso, Carlos; Algieri, Daniel (Cirugía del Uruguay, 1995)
total of 102 cases of abdominal trauma treated at Hospital Municipal de Morón, Province of Buenos Aires, Argentina, between January 1989 and December 1992. The Moore classification far hepatic lesions was employed. 75% of the hepatic traumas were open ones; 80% of them were caused by firearms. The majar percentage of injuries corresponded to males; the average age corresponded to the 20-29 and 30-39 ranges. The predominant access was supra and infraumbilical median incisions and hepatic segments 11 and 111 simultaneously were the most frequently injured. Surgical tactics and associated lesions are explained. Complications of different degrees of importance were found in 75% of the cases.